Studi Penentuan Skala Prioritas Berdasarkan Kinerja Jaringan Irigasi Pada Jaringan Irigasi Batujai, Gde Bongoh, Dan Sidemen Di Kabupaten Lombok Tengah - Supriyono, Supriyono; Rispiningtati, Rispiningtati; Montarcih, Lily; Sayekti, Rini Wahyu (Fakultas Teknik, Universitas Brawijaya, 2013)
West Nusa Tenggara Province is a national food barn, and it is not surprising because of most people in this province are working in agriculture sector. The Ministry of Public Work, through its Public Work Official at West Nusa Tenggara Province and also River Region Bureau of West Nusa Tenggara I, has allocated the budget to finance the irrigation network every year in order to improve agriculture production. This research is a case study of the performance of the irrigation network. The performance is measured to help the determination of the priority scale of the management of irrigation network. The study area is located at irrigation regions of Batujai, Gde Bongoh and Sidemen. These three regions are under the work region of Water Official of Central Lombok District. Batujai irrigation network has 3,315 ha wide with water sufficiency rate (Factor K) of 58.33 %. Gde Bongoh irrigation network has 2,644 ha wide with water sufficiency rate of 66.67 %. Sidemen irrigation network has 3,315 ha wide with water sufficiency rate of 95.83 %. The assessment methods are based on The Decree of The Minister of Public Work No.32/PRT/M/2007. Result of the assessment indicates that Batujai and Gde Bongoh irrigation network are in low performance category with the point 65,67% and 67,60% respectively.Therefore that need improvement on the area of increase the field of personnel management and organizational management of Farmer Water User Association (P3A). Whereas Sidemen irrigation network is in good performance category with the point of 73.68 %.Keywords: Priority Scale, Factor K, Water Sufficiency, Irrigation Performance